Spatio-Temporal Profiling of Metarhizium anisopliae—Responsive microRNAs Involved in Modulation of Plutella xylostella Immunity and Development - Junaid Zafar (MDPI AG, 2021)
Metarhizium anisopliae, a ubiquitous pathogenic fungus, regulates a wide array of the insect pest population. The fungus has been employed to control Plutella xylostella, an insecticide-resistant destructive lepidopteran pest, which causes substantial economic losses in crops worldwide. Integration of modern gene-silencing technologies in pest control strategies has become more crucial to counter pesticide-resistant insects. MicroRNAs (miRNA) play essential roles in the various biological process via post-transcriptional gene regulation. In the present study, RNA-seq analysis of control (CK36h, CK72h) and fungal-infected (T36h, T72h) midguts was performed to reveal underlying molecular mechanisms occurring in larval midgut at different time courses. We aimed at exploring M. anisopliae-responsive miRNAs and their target genes involved in development and immunity. After data filtration, a combined set of 170 miRNAs were identified from all libraries. Interestingly, miR-281, miR-263, miR-1, miR-6094 and miR-8 were listed among the most abundantly expressed conserved miRNAs. Furthermore, we experimentally studied the role of differentially expressed miR-11912-5p in regulating corresponding target trypsin-like serine proteinase (Px_TLSP). The luciferase assay (in vitro) revealed that miRNA-11912-5p significantly downregulated its target gene, suggesting it might play a crucial role in defense mechanism of P. xylostella against M.+ anisopliae infection. We used synthetic miRNA mimic/inhibitor (in vivo), to overexpress/silence miRNA, which showed harmful effects on larval duration, survival and adult fecundity. Additionally, fungal application in the presence of mimics revealed enhanced sensitivity of P. xylostella to infection. Our finding provides an insight into the relatively obscure molecular mechanisms involved in insect midgut during the fungal infection.